Distribution and source of hydrocarbons in the sediments of the Selangor River, Malaysia - Masood, Najat Abdullah Ebrahim (2017)
Environmental pollutants such as anthropogenic hydrocarbons (AHs) are known to result from increased urbanization and act as indicators of anthropogenic activity. Hydrocarbons contamination is a great global concern due to their negative effects on human health and environmental consequences, such as toxic, mutagenic, carcinogenic, teratogenic and hepatotoxic effects. Consequently, a clear understanding and monitoring of distribution, sources, pathways and fate in the environment and ecosystems of AHs is of high importance in sediment samples collected from Kuala Selangor River, which is located on the west coast of Peninsular Malaysia, in order to determine the distributions and sources of hopanes, alkanes, polycyclic aromatic hydrocarbons (PAHs), and linear alkylbenzenes (LABs) in four periods. The sediment samples were collected from the river and its estuary during the rainy inter-monsoonal period, the dry inter-monsoonal period, the North-East Monsoon (NEM) period, and the South-West Monsoon (SWM) period because during these periods the samples are expected to contain varying amounts of pollutants. The collected samples were homogenized, freeze-dried, extracted, cleanup, fractionated and analyzed using gas chromatography mass spectrometry. The results of this study revealed that the concentrations of PAHs for the 13 sampling sites pooled over the four studied periods ranged from 341.33 ng g-1 dw (in the SWM period) to 651.64 ng g-1 dw (in the wet inter-monsoon period) with the mean value of 471.05 ng g-1 dw. In other respects, the outcomes of the one-way ANOVA indicated that the differences between the PAHs among the sampling stations were significant (p < 0.05). The diagnostic ratios of individual PAHs in sediments indicated both petrogenic and pyrogenic origin PAHs with significant dominance of pyrogenic source. The comparison of PAHs with Sediment Quality Guidelines (SQGs) indicates that the levels of the PAHs in the surface sediments of Selangor River are unlikely to cause any adverse biological effects to the aquatic organisms, including those that are closely associated with sediments. No significant correlation was found between AHs and organic carbon, which means that the distribution of AHs was not affected by the organic carbon content. In the four studied periods, the concentrations of the LABs in Selangor River ranged from 23.70 to 113.30 ng g-1 dw with an arithmetical mean of 54.04 ± 22.34 ng g-1 dw. The average concentration of the total LABs was found to be higher in the wet season (65.20 ± 25.04 ng g-1 dw) than in the other seasons. The average values of the ratio of long-chain to short-chain LAB (L/S), C13/C12, and the ratio of Internal to External isomers (I/E) in the sediments of Selangor River during the four studied periods were 2.03 ± 1.06, 1.74 ± 0.28, and 0.6 ± 0.17, respectively, indicating inputs of LABs from direct wastewater discharges. The I/E ratio decreased from upstream to downstream of Selangor River. This indicates that the sedimentary LABs downstream of the river (estuary) were more degraded than those in the upstream. The concentrations of total alkanes (nC10-nC36) ranged from 967 to 3,711 μg g-1 dw in sediment samples. In addition, the results of this study indicated that the alkanes in the sediment samples originated from diverse sources. Fresh oil, terrestrial plants (riverine area), and heavy/degraded oil (estuarine area) were the predominant source of alkanes in sediments. The alkanes originating from higher plants were mostly predominant in sediments from the stations located in upper parts of the river. The levels of hopanes ranged from 235 to 1,044 ng g-1 dw in sediments. The C29/C30 hopanes ratios were similar with those of used crankcase oil and Middle East Crude Oil (MECO), suggesting MECO as a major source of petroleum hydrocarbons (PHCs) in the sediments of Selangor River. In sum, presence of selected hydrocarbons (PAHs, LABs, alkanes, and hopanes) in the sediments of Selangor River, Malaysia, was studied during four periods. The results show that the agricultural, urban, and industrial activities in the state of Selangor, coupled with a high population growth, have caused deterioration in the quality of its river water. The concentrations of the investigated hydrocarbons varied from sampling site to another and from one period to another. Further studies should be conducted to address this problem.